Development of principles and equipment for formation of signals for testing and monitoring the incoherent scatter radar - Емельянов, Л.Я. (Radiotekhnika, 2017)
Principles of testing the incoherent scatter (IS) radar are considered. The equipment for the formation of signals for testing the IS radar systems and monitoring the measurement of ionosphere parameters by the IS technique is proposed. Requirements to it were developed based on analysis of the characteristics of the IS signal. The equipment makes it possible to check fast the main parameters of radar systems and the accuracy of the ionospheric parameters such as the ion and electron temperatures and the ionosphere plasma drift velocity, as well as to test and optimize algorithms and programs for processing noise-like signals.